Development of a Learning Module for Poster Texts Containing Riau Malay Culture for MTs Grade 8 Students - Sari, Yulna Pilpa; Sinaga, Mangatur; Hermandra, Hermandra (Universitas Negeri Malang, 2024)
This research is motivated by the problem of the lack of availability of teaching materials. The main teaching materials used by students are student worksheets, while the supporting teaching materials are school textbooks. This research is a research and development using the Analyze, Design, Develop, Implement, and Evaluate approach. The purpose of this study is to produce and describe the development of a learning module for poster texts containing Riau Malay culture. Based on the research and development conducted, it is known that the analysis of the needs of the learning module for poster texts containing Riau Malay culture is categorized as very much needed. Furthermore, based on the high level of need, a product design and development in the form of a module was prepared. Overall, the validation results of the learning module for poster texts containing Riau Malay culture are categorized as very good and can be tested. The pretest and posttest values obtained from the results of the trial were then tested to determine the significance of product use. Based on the tests carried out, significant differences were obtained. Furthermore, at the evaluation stage, it was carried out based on assessments from expert validators, assessments of Indonesian language teachers, and student assessments. Overall, the assessments from the three aspects were categorized as very good. Thus, the learning module for poster texts containing Riau Malay culture that was developed is suitable for use in learning poster texts. Abstrak Penelitian ini dilatarbelakangi oleh permasalahan kurangnya ketersediaan bahan ajar. Bahan ajar utama yang digunakan oleh siswa adalah lembar kerja siswa, sedangkan bahan ajar pendukungnya ialah buku paket sekolah. Penelitian ini merupakan penelitian dan pengembangan dengan menggunakan pendekatan Analyse, Design, Develop, Implement, dan Evaluate. Tujuan penelitian ini ialah untuk menghasilkan dan mendeskripsikan pengembangan modul pembelajaran teks poster bermuatan budaya Melayu Riau. Berdasarkan penelitian dan pengembangan yang dilakukan, diketahui analisis kebutuhan modul pembelajaran teks poster bermuatan budaya Melayu Riau berkategori sangat butuh. Selanjutnya, berdasarkan tingginya tingkat kebutuhan tersebut, disusunlah sebuah rancangan dan pengembangan produk berupa modul. Secara keseluruhan hasil validasi modul pembelajaran teks poster bermuatan budaya Melayu Riau berkategori sangat baik dan dapat dilakukan uji coba. Nilai pretest dan posttest yang didapatkan dari hasil uji coba selanjutnya diuji untuk mengetahui signifikansi penggunaan produk. Berdasarkan uji yang dilakukan didapatkan perbedaan yang signifikan. Selanjutnya pada tahapan evaluasi, dilakukan berdasarkan penilaian dari para validator ahli, respons pengguna (guru dan siswa). Secara keseluruhan penilaian dari tiga aspek tersebut berkategori sangat baik. Dengan demikian modul pembelajaran teks poster bermuatan budaya Melayu Riau yang dikembangkan layak untuk digunakan dalam pembelajaran teks poster.